People’s Participation and Rural Development: Nepal’s Case - Umesh Acharya, (Interdisciplinary Journal of Management and Social Sciences, 2022)
This paper analyzes the relationship between people’s participation and rural development taking the case of Nepal. We use secondary data from publications and research reports. The paper concludes that in developing countries like Nepal involvement of people’s participation is very important. People’s participation in Nepal is limited only for elite people but not for people from deprived communities. Though, people’s participation has increased in Nepal over the last few decades but people from backward society are not participating to the same extent of high income group which creates conflicts in society. Now government, political leaders, civil societies, development workers should look towards bringing backward communities in mainstream development activities for the betterment of them and the nation.